Effect of computer use on physician-patient communication using interviews: A patient perspective. (May 2019) - Antoun, Jumana; Hamadeh, Ghassan; Romani, Maya
Highlights: Patients have positive attitude towards the use of computers in the clinic and its impact on communication skills. Paying attention rather than eye contact is what matters for the patients. New skills for better communication skills should be learned for optimal use of the computers in the clinic. Abstract: Background: A commonly stated barrier to adoption of electronic medical record (EMR) is fear of a negative impact on physician-patient communication. Systematic reviews have shown that there is limited literature addressing the patients' perspective as compared to the physicians' perspectives. Aim: This study aims to understand patients' perspective on the effect of EMR on physician-patient communication in an ambulatory setting. Design and settings: This is a qualitative study using semi-structured interviews with 49 patients at a multi-physician family medicine clinic in a large academic medical center in Beirut, Lebanon. Materials and methods: At the end of the visit with the physicians, the patients were approached by the clinical assistant to conduct an interview concerning the patient-doctor communication in the presence of electronic medical record. The interview was conducted in a private office by an experienced researcher. Results: Almost all patients reported that computer use during the encounter did not affect the quality of communication with their physician. Five themes emerged from the analysis of the interviews: (1) EMR use in clinic is considered a necessity; (2) EMR use by physicians is efficient in record keeping and information retrieval; (3) physicians balance between using the computer and paying attention to patients; (4) computer use by physicians might affect communication about personal and intimate issues; (5) concomitant computer use while listening to the patient was not considered disturbing. Conclusions: Most patients appreciated EMR use by physicians during the clinical encounter and acknowledged its benefits despite the presence of some concerns. Most patients did not consider that EMRs affect communication with physicians negatively especially when used in a balanced manner. Attention rather than eye contact is what mattered the most for patients.